Kinetics and Thermodynamics of Oil Extraction from Jatropha curcas L. Using Ethanol as a Solvent - Silmara Bispo dos Santos; Marcio Arêdes Martins; Ana Lívia Caneschi; Paulo Rafael Morette Aguilar; Jane Sélia dos Reis Coimbra (International Journal of Chemical Engineering)
In the study the yield and kinetic and thermodynamic parameters of the oil extraction process from Jatropha curcas L. using ethanol as a solvent were evaluated for different temperatures, moisture contents of the solid phase, and particle sizes. The extraction process yield increased with contact time of solid particles with the solvent until reaching equilibrium (saturation of the solvent), for all the temperatures, moisture contents, and average particle sizes. These parameters significantly influenced (95% confidence) the extracted oil yield. A convective mass transfer model was used to simulate the extraction process and estimate the kinetic and thermodynamic parameters. For all conditions evaluated, values of oil yield in the liquid phase close to equilibrium were obtained in approximately 20 min. The variations of enthalpy and entropy were positive, indicating that the process is endothermic and irreversible. Values obtained for the variation in Gibbs free energy showed that the extraction process using ethanol as a solvent is spontaneous and thermodynamically favorable for the moisture content of 0%, where the smaller the average particle size the greater the spontaneity of the process.